Terms of frequent use in topics of pasture production and utilization (Semiárida, 2018)
The aim of this work was to elaborate a glossary which facilitates the access to a single and concise definition of key terms used by the discipline of Pasture Production and Utilization. A catalogue is presented considering the most relevant terms and concepts of major approval by consensus, which are addressed by literature and internationally accepted. A reference to the English equivalent term was made for them, identifying those ones with imprecise or wrong use.
Keywords: glossary; forages; grazing